2023
DOI: 10.2174/1389200224666230815122312
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Insights into the Mechanism of Modulatory Effects of Proton Pump Inhibitors on P-glycoprotein Mediated Drug Transport of Palbociclib and Ribociclib

Abstract: Background: Palbociclib and ribociclib are substrates of efflux transporter, P-glycoprotein plays a key role in absorption and transport of these drugs. Proton pump inhibitors, when co-administered with them are known to show inhibitory effect on P-glycoprotein. Objective: Therefore, this study aims to investigate the role of proton pump inhibitors in inhibition of P-glycoprotein mediated efflux of palbociclib and ribociclib. Method: A combined approach of molecular docking and ex vivo everted gut sac mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Palbociclib and Ribociclib act as substrates for the efflux transporter P-glycoprotein (Pgp), and, as a matter of fact, PPIs are known as moderate inhibitors of P-gp [34]. In ex vivo studies, it was found that rabeprazole and omeprazole decreased the absorptive permeability of Palbociclib by 3.04-and 1.26-fold, respectively, and of Ribociclib by 1.76and 2.54-fold, respectively, highlighting the ability of PPIs to inhibit the P-gp-mediated efflux of both CDKIs [35]. Although the PPI inhibition of CDKI efflux could theoretically increase the concentration of a CDKI, thereby increasing drug toxicity, our meta-analysis demonstrated that there was no difference in dose reduction due to drug toxicity between PPI users and non-users.…”
Section: Discussionmentioning
confidence: 99%
“…Palbociclib and Ribociclib act as substrates for the efflux transporter P-glycoprotein (Pgp), and, as a matter of fact, PPIs are known as moderate inhibitors of P-gp [34]. In ex vivo studies, it was found that rabeprazole and omeprazole decreased the absorptive permeability of Palbociclib by 3.04-and 1.26-fold, respectively, and of Ribociclib by 1.76and 2.54-fold, respectively, highlighting the ability of PPIs to inhibit the P-gp-mediated efflux of both CDKIs [35]. Although the PPI inhibition of CDKI efflux could theoretically increase the concentration of a CDKI, thereby increasing drug toxicity, our meta-analysis demonstrated that there was no difference in dose reduction due to drug toxicity between PPI users and non-users.…”
Section: Discussionmentioning
confidence: 99%